The Role of Brand Awareness in Mediating Social Media Marketing on Purchase Intention of Converse Shoes - I Gede Yuda Hariyawan; Ni Wayan Ekawati; Ni Made Rastini; I Gede Riana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Converse is a canvas shoe that is very popular nowadays and is always a trend among young people. This study aims to measure the effectiveness of social media marketing variables on purchase intention by using brand awareness variables as a mediator, so this study uses consumer behavior theory. This study uses a sample of 100 respondents taken using the non-probability sampling method with purposive sampling technique. The data in this study were collected using a questionnaire method that was distributed offline to respondents. The data that has been collected is then analyzed by the classical assumption test, path analysis test, and testing the role of mediating variables using the Sobel test. The results of this study indicate that social media marketing has a positive and significant effect on purchase intention, social media marketing has a positive and significant effect on brand awareness, brand awareness has a positive and significant effect on purchase intention, and brand awareness is able to partially mediate the influence of social media marketing on purchase intention. Converse shoe management is expected to continue to provide complete information about Converse products through social media and maintain brand awareness of Converse shoes to increase purchase intention.